Rural criminal collaborations and the food crimes of the countryside: realist social relations theory of illicit venison production - Goodall, Orlando (Crime, law and social change, 2022)
This article provides the first comprehensive criminological account of routinised illicit venison production in rural England. In doing so an epistemological reformulation and conceptual clarification of the overlooked problem is advanced, using extended fieldwork and a novel theoretical framework. The account of offending is refined to a type of illicit rural food enterprise supply chain misconduct, actualised by un-regulated industry processes. This kind of food crime is shown to be reliant upon suspects’ connectivity with small to medium food business operations and the routines of rural occupations. Such relations with licit rural-centric commerce are the necessary conditions of offending, which are enabled by the contingent conditions of sub-optimal game meat traceability systems and an absence of regulatory oversight at critical junctures. An outcome that is structurally inscribed into legislation and induces non-compliance. The article addresses the current lacuna of research on venison meat food crimes in the British context and advances an innovative realist social relations theory to explain the crime commissioning process.